Writing About the Silence: Identifying the Language of Ostracism. (October 2020) - Klauke, Fabian; Müller-Frommeyer, Lena C.; Kauffeld, Simone
Autobiographical reports of episodes of ostracism and social inclusion were analyzed in two separate samples (German N = 93; English N = 243) using the Linguistic Inquiry and Word Count (LIWC) software. Recalling ostracism was associated with the use of more first-person singular pronouns, fewer first-person plural pronouns, and more complex language. These findings could reflect ostracism inducing a self-focus and putting high cognitive load on its targets. This study provides a first step to establish linguistic analysis as a tool for the research of social exclusion.